The Impact of CO2 Enrichment on Biomass, Carotenoids, Xanthophyll, and Mineral Content of Lettuce (Lactuca sativa L.) - Jake Holley; Neil Mattson; Eyosias Ashenafi; Marianne Nyman (Horticulturae, 2022)
Carbon dioxide (CO2) concentrations affect the growth rate of plants by increasing photosynthesis. Increasing CO2 in controlled environment agriculture (CEA) provides a means to boost yield or decrease daily light integral (DLI) requirements, potentially increasing profitability of growing operations. However, increases in carbon dioxide concentrations are often correlated with decreased nutritional content of crops. The objectives of this experiment were to quantify the effects of carbon dioxide on the growth, morphology, and nutritional content of two lettuce varieties, ‘Rex’ and ‘Rouxai’ under four CO2 concentrations. Applied CO2 treatments were 400, 800, 1200, and 1600 ppm in controlled environment chambers with identical DLI. Lettuce was germinated for eight days in a greenhouse, then transplanted into potting mix and placed in a growth chamber illuminated by fluorescent lights. After 21 days, lettuce was destructively harvested, and fresh weight and plant volume were measured. Anthocyanins, xanthophylls, chlorophyll, and mineral concentration were measured. The lettuce fresh and dry weight increased with increasing CO2 concentrations, with the greatest increases observed between 400 and 800 ppm, and diminishing increases as CO2 concentration further increased to 1200 and 1600 ppm. Violaxanthin was observed to decrease in ‘Rouxai’ with increasing CO2 concentration. Largely, no significant differences were observed in lutein, anthocyanins, and mineral content. Overall, increasing concentrations of carbon dioxide can significantly increase the yield for lettuce in controlled environments, while not significantly reducing many of the nutritional components.